Multipotent stem cells of the heart—do they have therapeutic promise? - Leite, Camila F.; Almeida, Thalles R.; Lopes, Carolina S.; Dias da Silva, Valdo J. (Frontiers in Physiology, 2015)
The last decade has brought a comprehensive change in our view of cardiac remodeling processes under both physiological and pathological conditions, and cardiac stem cells have become important new players in the general mainframe of cardiac homeostasis. Different kinds of cardiac stem cells has been identified with variable abilities to differentiate into the three major cardiac lineages, myocytes, endothelial cells or smooth muscle cells. Physiologically, cardiac stem cells appear to contribute to cardiac homeostasis through continual cellular turnover. Pathologically, these cells exhibited a high level of proliferative activity in an apparent attempt to repair acute cardiac injury, indicating that these cells have regenerative potential, albeit limited. In addition to these cardiac stem cells, mesenchymal stem cells represent another multipotent cellular population in the heart that are located in regions near pericytes and exhibit regenerative, angiogenic, antiapoptotic, and immunosuppressive properties. The discovery of these resident cardiac stem cells was followed by a number of experimental studies in animal models of cardiomyopathies, in which cardiac stem cells were tested as a therapeutic option to overcome the limited transdifferentiating potential of hematopoietic or mesenchymal stem cells derived from bone marrow. The promising results of these studies prompted clinical studies of the role of these cells, which have demonstrated the safety and practicability of cellular therapies for the treatment of heart disease. However, questions remain. The aim of the present review was to discuss the multitude of different cardiac stem cells that have been identified, their possible functional roles in the cardiac regenerative process, and their potential therapeutic uses in treating cardiac diseases.